1987
DOI: 10.1073/pnas.84.14.5024
|View full text |Cite
|
Sign up to set email alerts
|

Platinum-DNA adducts in leukocyte DNA correlate with disease response in ovarian cancer patients receiving platinum-based chemotherapy.

Abstract: Fifty-five ovarian cancer patients receiving platinum drug-based chemotherapy have been studied prospectively to determine the extent of formation of the bidentate intrastrand adducts of diammineplatinum covalently attached to the N7 positions of adenosine and/or guanosine in leukocyte DNA. Data for clinical response, obtained from medical records, were then correlated with the adduct values. Patients were treated with platinum-based single-agent or combination chemotherapy containing cis-diamminedichloroplati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
95
0

Year Published

1994
1994
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 191 publications
(100 citation statements)
references
References 21 publications
5
95
0
Order By: Relevance
“…Therefore, altered NER pathway activity may correlate with improved response to platinum-based chemotherapy. [4][5][6][7] Variations in NER pathway activity can occur genetically through single-nucleotide polymorphisms (SNPs). SNPs are base-pair (bp) changes that achieve a population frequency of at least 1%.…”
mentioning
confidence: 99%
“…Therefore, altered NER pathway activity may correlate with improved response to platinum-based chemotherapy. [4][5][6][7] Variations in NER pathway activity can occur genetically through single-nucleotide polymorphisms (SNPs). SNPs are base-pair (bp) changes that achieve a population frequency of at least 1%.…”
mentioning
confidence: 99%
“…Together these data suggest that adduct levels after carboplatin are determined primarily by factors other than drug exposure, which could include drug uptake, reaction with glutathione or other inactivation mechanisms and DNA repair (de Graeff et al, 1988). As discussed above, Pt-DNA adduct levels in PBLs and tumour response have been shown to be related in a number of studies (Reed et al, 1986(Reed et al, , 1987(Reed et al, , 1990Fichtinger-Schepman et al, 1990;Ma et al, 1994). If low adduct levels in poor responders are due to an intracellular factor in the PBLs then the same factor must be operating in the tumour cells, i.e.…”
Section: Discussionmentioning
confidence: 95%
“…Preliminary clinical results with immunoassays for Pt-DNA adducts support the suggestion that adduct formation may relate to anti-tumour activity. Specifically, Reed and colleagues (Reed et al, 1986(Reed et al, , 1987(Reed et al, , 1988(Reed et al, , 1990 have reported that adduct levels in peripheral blood leucocytes (PBLs) correlate with response in patients receiving either cisplatin-or carboplatin-based therapy. A major limitation of these studies is that the influence of pharmacokinetic variation was not investigated.…”
mentioning
confidence: 99%
“…These adducts are responsible for the cytotoxicity of the drug, and clinical outcome seems to be correlated with the level of platinum-DNA adducts in the circulation (Reed et al, 1987;Bosken et al, 2002). Additionally, these adducts are mainly repaired by the NER pathway (Park et al, 2001).…”
Section: Discussionmentioning
confidence: 99%